2022
DOI: 10.1186/s12905-022-01736-8
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in contraceptive use among female adolescents in south Asian countries: a decomposition analysis

Abstract: Background Contraceptive knowledge and use has been an emerging topic of interest in adolescents in Asia. This study quantified the contribution of the socioeconomic determinants of inequality in contraceptive use among currently married female adolescents (15–24) in four south Asian countries: India, Bangladesh, Nepal and Pakistan. Data and methods The data of Demographic Health Survey (DHS) for four South Asian countries, i.e. India (NFHS 2015–16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…The use of contraception among female adolescents is low and socioeconomic factors contributed substantially to it. 24 The results of this study revealed that adolescents residing in rural areas showed a low preponderance of using contraception. Uneducated women, women from the poorest strata of society and belonging to disadvantageous social groups like the OBCs, used less contraception as a result of their socioeconomic profile.…”
Section: Discussionmentioning
confidence: 70%
“…The use of contraception among female adolescents is low and socioeconomic factors contributed substantially to it. 24 The results of this study revealed that adolescents residing in rural areas showed a low preponderance of using contraception. Uneducated women, women from the poorest strata of society and belonging to disadvantageous social groups like the OBCs, used less contraception as a result of their socioeconomic profile.…”
Section: Discussionmentioning
confidence: 70%
“…Despite being disadvantaged and facing various socio-economic challenges, it was found that illiterate women were using modern contraceptive methods more frequently compared to their literate counterparts, the possible reason could be the higher sterilization rate and the financial incentive associated with it. However previous studies have suggested that the higher education level is associated with the modern contraceptive use [ 9 , 22 , 26 ]. Tribal women following Hindu religion were associated with the increased modern contraceptive use, however previous studies also confirms the same [ 27 , 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…The FPBC could potentially lead to increased savings, reduced mortalities, and contribute towards long-life span, attaining the SDGs and economic growth and development in the long run. The FPBC could also be used as one of the panaceas to the worldwide gross inequalities in accessing modern contraception since it covers the financial risk of out-of-pocket expenditure on modern contraception among marginalized groups [8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The inequality of access to modern contraception is a reality not only in low-income countries but also in highincome countries. Different studies have shown that the utilization of long-term modern contraception methods varies across the area (region of residence), age, and socioeconomic status -with poor access among low-income earners, the unemployed, and rural dwellers [8][9][10][11][12][13][14]. The question researchers and policymakers worldwide should be asking is, what interventions or strategies are currently in place to reduce inequalities in accessing modern contraception?…”
Section: Introductionmentioning
confidence: 99%